The Role of Wearable Devices in Cardiovascular Monitoring of Athletes: Implications for Sudden Cardiac Death Prevention - Wilczynski, Rafal; Samp, Nikola; Foryński, Jędrzej; Stachurska, Michelle; Trzepizur, Paweł; Zera, Kamila; Bekrycht, Beniamin; Piekarska, Weronika; Radiczew, Konstancja; Rogala, Karolina (Journal of Education, Health and Sport, 2026)
Background. Sudden cardiac arrest (SCA) and sudden cardiac death (SCD) in athletes are rare but devastating events. Traditional prevention relies on preparticipation cardiovascular screening, which may not identify intermittent or exercise-induced abnormalities. Wearable technologies offer continuous cardiovascular monitoring and may support early detection of potential abnormalities. Aim. To evaluate the role of wearable devices in cardiovascular monitoring of athletes and their potential contribution to SCA/SCD prevention. Material and methods. A narrative review was performed using PubMed, Scopus, and Google Scholar. Original studies, reviews, and consensus statements on wearable devices, arrhythmia detection, heart rate variability, and SCA/SCD in athletes were analyzed qualitatively, with emphasis on recent literature. Results. Wearable devices based on photoplethysmography (PPG) and wearable electrocardiography (ECG) allow monitoring of cardiovascular parameters during daily activity and exercise. Wearable ECG offers greater diagnostic value for arrhythmia detection, whereas PPG enables long-term monitoring but is more susceptible to artifacts. Heart rate variability and other derived metrics may reflect autonomic regulation, although their value in predicting serious cardiac events remains uncertain. Current evidence supports wearables as adjunctive tools for symptom evaluation and longitudinal monitoring rather than standalone preventive methods. Conclusions. Wearable technologies show promise for cardiovascular monitoring in athletes but should currently complement rather than replace established screening strategies. Further prospective studies and standardized clinical guidelines are needed to define their role in sports cardiology.